Durability of GFRP-concrete adhesively bonded connections: Experimental and numerical studies. (1st August 2018) - A. Gonilha, José; R. Correia, João; A. Branco, Fernando; Sena-Cruz, José
Highlights: Accelerated ageing has deleterious effects on stiffness but not on strength. Smoother stress distribution counterbalances peak strength degradation. FE models with bi-linear interface laws are able to simulate experimental behaviour. Degradation has smalleffects on the performance of GFRP-SFRSCC hybrid structures. Abstract: In order to overcome the main mechanical drawbacks of GFRP profiles, namely their high deformability and proneness to instability phenomena, several GFRP-concrete hybrid solutions comprising bonded connections with epoxy adhesive have been proposed. Although being able to provide almost full interaction at the GFRP-concrete interface(s) (at least in the short-term), there is very little information about the durability of such connection systems, which raises concerns about the long-term performance of hybrid structural solutions. This paper presents experimental and numerical investigations on the durability of adhesively bonded connections between pultruded GFRP profiles and steel fibre reinforced self-compacting concrete (SFRSCC). GFRP-SFRSCC specimens were first subjected to accelerated ageing, involving thermal and wet-dry cycles, and then subjected to push-out tests. The accelerated ageing did not have significant influence on the strength of the GFRP-SFRSCC connection; however, it had a very deleterious effect on its stiffness. The numerical study included the development of finite element models of the specimens tested. Using bi-linear bond-slip laws, it was possible to simulate the test results with good accuracy. In the final part of the paper, the influence of the interface stiffness reduction on the deformability of a real hybrid structure (the São Silvestre footbridge) is analysed. Although the stiffness of the GFRP-SFRSCC interface is considerably reduced by the ageing processes, this results in a very small increase of the overall mid-span deflections of the footbridge.